EVALUASI APLIKASI MOBILE DESAIN MENGGUNAKAN METODE NIELSEN’S ATTRIBUTES OF USABILITY - Hulliya, Khadijah; Amanda, Aliza Fatha (LPPM Universitas Abdurrab, 2024)
To achieve good software standards, software quality testing is required, including usability. One of the factors that determine software quality is ease of use. In this study, the authors conducted research on the Canva application. This application has been downloaded 100 million times by users on Google Playstore. In this study, the authors used the usability testing method. The data used in this study were obtained through questionnaires and literature studies. The purpose of this research is to find out the results of the usability evaluation of the Canva application. Data was obtained through literature research and Nielsen's questionnaire on usability features. The use of Nielsen's Usability Attributes questionnaire method, which has five indicators: Learnability (easy to learn), Efficiency (efficient), Memorability (easy to remember), Errors (failure), and Satisfaction (satisfaction), the purpose of this study is to determine the results of usability evaluation on the Canva application. Testing with the NAU method gives an average result of 4.02 (Agree) from a rating scale of 5 (Strongly Agree). That is, users agree that the function runs well.